Gone with the wind - Selznick, David O., 1902-1965.; Howard, Sidney Coe, 1891-1939.; Fleming, Victor, 1889-1949.; Gable, Clark, 1901-1960.; Leigh, Vivien, 1913-1967.; Howard, Leslie, 1893-1943.; De Havilland, Olivia; Mitchell, Thomas, 1892-1962.; McDaniel, Hattie, 1895-1952.; McQueen, Butterfly; Mitchell, Margaret, 1900-1949.; Selznick International Pictures; et al. (Burbank, CA : Warner Home Video, 1999)
Presents the story of Scarlett O'Hara, a Southern belle who enjoys her socialite lifestyle and the attention of many eligible single rich men. This idyllic lifestyle is shattered by the onset of the U.S. Civil War that eventually reduces her home to near ruins. Robbed of the luxuries she loved, she vows to grow strong so she will never be poor again. She begins to ruthlessly climb to the top of the new social order. Scarlett also has a complex, love-hate relationship with Rhett Butler, a man of questionable morals.
At head of title on container: David O. Selznick's production of Margaret Mitchell's Gone with the wind.
Based on the novel by Margaret Mitchell.
Originally produced as motion picture in 1939.
Special features: scene access, theatrical trailer.
Photography, Ernest Haller, Ray Rennahan; special photographic effects, Jack Cosgrove; production design, William Cameron Menzies; supervising film editor, Hal C. Kern; music, Max Steiner.
Clark Gable, Vivien Leigh, Leslie Howard, Olivia De Havilland, Thomas Mitchell, Hattie McDaniel, Butterfly McQueen.
Keywords: Plantation life -- Georgia -- Drama; Reconstruction -- Georgia -- Drama; O'Hara, Scarlett (Fictitious character) -- Drama; Georgia -- History -- Civil War, 1861-1865 -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama; Feature films; War films; Video recordings for hard of hearing people